Factors Associated with Sexual Education Provided by Parents to Adolescents Aged 11-14 Years in Durian Village - Diah Sri Wulandari (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Sexual issues are important to provide sexual education for children to straighten children's sexual perceptions and behavior to be more positive. Possible reactions related to parental knowledge, parental attitudes, parental communication, parental education level, parental taboo perception and parental income. The purpose of this study was to determine the factors associated with the provision of sexual education by parents by adolescents aged 11-14 years in Durian Village. This study used a cross-sectional research design with Chi Square test with 95% confidence level. The population in this study were 1,685 families and a sample of 94 people divided into 5 hamlets. The results of this study indicate that there is a relationship between parental knowledge and the provision of sexual education (p value = 0.001), parental education with the provision of sexual education (p value = 0.009), parental attitudes with the provision of sexual education (p value). =0.008) and the perception of taboo with the provision of sexual education (p value = 0.011). Variables that have no relationship are communication and parental income. Parents can increase knowledge about sexuality so that parents can understand the importance of sexual education given to their childrenPendidikan seksual anak penting diberikan untuk meluruskan persepsi dan perilaku seksual anak menjadi lebih positif. Kemungkinan hal yang menghambat pendidikan seksual terhadap anak yaitu pengetahuan orang tua yang rendah, sikap orang tua, komunikasi orang tua dengan anak tidak terbuka, tingkat pendidikan orang tua rendah, persepsi tabu orang tua dan pendapatan orang tua. Tujuan penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan pemberian pendidikan seksual oleh orang tua oleh remaja usia 11-14 tahun di Desa Durian. Penelitian ini menggunakan rancangan penelitian cross-sectional dengan uji Chi Square dengan tingkat kepercayaan 95 %. Populasi dalam penelitian ini sebanyak 1.685 keluarga dan sampel sebanyak 94 orang yang terbagi menjadi 5 dusun. Hasil penelitian ini menunjukan bahwa terdapat ada hubungan antara pengetahuan orang tua dengan pemberian pendidikan seksual (p value=0,001), pendidikan orang tua dengan pemberian pendidikan seksual (p value=0,009), sikap orang tua dengan pemberian pendidikan seksual (p value=0,008) dan persepsi tabu dengan pemberian pendidikan seksual (p value=0,011). Variabel yang tidak ada hubungan yaitu komunikasi dan pendapatan orang tua. Bagi orang tua dapat meningkatkan pengetahuan mengenai seksual agar orang tua bisa memahami pentingnya pendidikan seksual yang dapat diberikan diberikan kepada anak mereka.